2012
DOI: 10.1007/s13191-012-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete Denture Impression Techniques Practiced by Private Dental Practitioners: A Survey

Abstract: Impression making is an important step in fabricating complete dentures. A survey to know the materials used and techniques practiced while recording complete denture impressions was conducted. It is disheartening to know that 33 % practitioners still use base plate custom trays to record final impressions. 8 % still use alginate for making final impressions. An acceptable technique for recording CD impressions is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…Various techniques and materials have been proposed to make a good impression for fabricating a complete denture. The most commonly used preliminary impression material in this survey was impression compound (78%); irreversible hydrocolloid was used by only 20% [ (Kakatkar, 2012)]. Another survey of four major Indian cities showed that a majority (71%) use alginate for preliminary impressions [ (Gambhir et al, 2018)].…”
Section: Discussion :-mentioning
confidence: 99%
“…Various techniques and materials have been proposed to make a good impression for fabricating a complete denture. The most commonly used preliminary impression material in this survey was impression compound (78%); irreversible hydrocolloid was used by only 20% [ (Kakatkar, 2012)]. Another survey of four major Indian cities showed that a majority (71%) use alginate for preliminary impressions [ (Gambhir et al, 2018)].…”
Section: Discussion :-mentioning
confidence: 99%
“…This finding coincided with the findings from studies conducted among practioners in South East Asia. 23,27 The possible explanation for the preferred use of zinc oxide eugenol in this region could be its cost effectiveness and the difference in teaching and training in dental schools.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,12,14,15 No entanto, em estudos realizados na Índia e no Paquistão, a godiva é também utilizada. 16,17 Esta tem caído em desuso, devido à sua dificuldade de manuseamento e tempo de trabalho requerido, por oposição ao alginato. 5,8,[17][18][19][20][21] Nas impressões definitivas verificou -se que a técnica de impressão mais utilizada foi a funcional, seguida das técnicas mucostática e de pressão seletiva.…”
Section: Discussionunclassified
“…Tal como em Portugal, o mesmo se verifica em diversos outros paí-ses. 4,14,16,22 Apesar disso, no Paquistão, Médicos Dentistas Generalistas não utilizam, já Médicos Dentistas Especialistas preferiam o uso de espaçador. 17 O seu uso nestas moldeiras leva a uma redução da pressão exercida sobre as cristas alveolares.…”
Section: Discussionunclassified